Influence of Internal Locus of Control and External Locus of Control on Job Satisfaction at PT Bank Rakyat Indonesia (Persero) Kendal Branch Office - Mulyana, Dewi Shinta; Setiyadi, Dody -; Widyanti, Dika Vivi; Azizah, Azizah - (Admisi dan Bisnis, 2024)
Human Resources play a pivotal role in ensuring a company's success. Favorable working conditions foster employee satisfaction and subsequently augment work productivity. This study endeavors to explore the influence exerted by internal and external locus of control on the work satisfaction levels at PT Bank Rakyat Indonesia (Persero) Kendal Branch. The study encompasses 110 employees from PT Bank Rakyat Indonesia (Persero) Kendal Branch, who were selected using the Disproportionate stratified sampling technique. Data collection was facilitated through questionnaires and observations. Multiple linear regression analysis was employed to analyze the data